Unifying nucleation and crystal growth mechanisms in membrane crystallisation - Mapetere, A.; Di Profio, Gianluca; Curcio, Efrem; Campo Moreno, Pablo; McAdam, Ewan J. (Elsevier, 2025)
While several mechanisms have been proposed to describe crystallisation processes in membrane distillation, it has not been possible to provide a definitive description since the nucleation kinetics are difficult to measure. This study therefore introduced non-invasive techniques to measure induction time within two discrete domains (the membrane surface and bulk solution) and was complemented by the introduction of a modified power law relation between supersaturation and induction time, that enables mass and heat transfer processes in the boundary layer to be directly related to classical nucleation theory (CNT). Temperature (T, 45–60 °C) and temperature difference (ΔT, 15–30 °C) were used to adjust boundary layer properties, which established a log-linear relation between the nucleation rate and the supersaturation level in the boundary layer at induction, which is characteristic of CNT. Crystal size distribution analysis demonstrated how nucleation rate and crystal growth rate could be adjusted using ΔT and T respectively. Consequently, ΔT and T can be used collectively to fix the supersaturation set point within the boundary layer to achieve the preferred crystal morphology. However, at higher supersaturation levels, scaling was observed. Discrimination of the primary nucleation mechanisms, using measured induction times, revealed scaling to be formed homogeneously, which indicates exposure of the pores to extremely high supersaturation levels. Morphological analysis of scaling indicated growth to be dominated by secondary nucleation mechanisms, that resulted in a habit that is distinctive from the crystal phase formed in the bulk solution. From this analysis, a critical supersaturation threshold was identified, below which kinetically controlled scaling can be ‘switched-off’, leaving crystals to form solely in the bulk solution comprising the preferred cubic morphology. This study serves to unify understanding on nucleation and growth mechanisms to enhance control over crystallisation in membrane systems.
Keywords: Metastable zone; Temperature and temperature difference; Zero liquid discharge; Brine; Distillation; 40 Engineering; Chemical Engineering; 34 Chemical sciences